Differentiated Learning in English for Specific Purposes (ESP) Class: A Students’ Perception Study - Apriana Diana; Muhammad Daffa Saptrian; G. K. Chithra (English Language in Focus (ELIF), 2025)
Educational transformation driven by Indonesia’s Merdeka Curriculum has shifted higher education toward more inclusive and learner-centered pedagogies. Within this reform agenda, differentiated learning (DL) has emerged as a key approach to address variations in students’ abilities, interests, and learning profiles. Nevertheless, empirical evidence on the application of DL in English for Specific Purposes (ESP) instruction at the tertiary level, particularly within engineering programs, remains limited. This study investigates engineering students’ perceptions of differentiated learning and examines its relationship with learner engagement and perceived ESP learning effectiveness. Participants were 68 first-year Mechanical Engineering students who completed a 30-item Likert-scale questionnaire adapted from established DL and ESP frameworks. The instrument demonstrated high internal reliability (Cronbach’s α = 0.86). Data were analyzed using descriptive and correlational statistics with SPSS 26. Findings reveal that students reported highly positive perceptions of differentiated learning (M = 4.21, SD = 0.43), with significant positive correlations between DL and engagement (r = 0.63, p < 0.05) and between DL and perceived learning effectiveness (r = 0.59, p < 0.05). These results suggest that differentiated learning promotes inclusivity, motivation, and disciplinary relevance in ESP contexts. The study provides empirical support for differentiated learning as a pedagogical framework linking language learning with professional competence, offering insights for curriculum design, teacher development, and higher education policy committed to responsive and personalized learning. Keywords: Differentiated instruction, English for Specific Purposes (ESP), Students’ perceptions, Engineering students.